Comparative analysis of intestinal microbiome of local cattle and Aberdeen Angus cattle imported to Kazakhstan - A. T. Daugaliyeva; S. T. Daugaliyeva; M. A. Kineev; B. S. Aryngaziyev; A. I. Sembaeva; T. A. Lavrentieva (Ветеринария сегодня)
Animal microbiome plays a significant role in all the vital body processes. Studying the microbiome is essential for gaining a detailed insight into the interactions among microorganisms inhabiting a certain organ and their relationship with macroorganism cells. Evaluating the state of animal microbial community and its function can provide an invaluable assistance in seeking new strategies to improve feed efficiency and maintain cattle health. The aim of the study was to compare the taxonomic structure of the intestinal microbiome of Aberdeen Angus cattle imported to Kazakhstan with that of local breed cows using next generation sequencing technology. The tests of fecal samples allowed for determination of the complete microbial composition of animal intestinal contents, while leaving out the preliminary stage of microbiological cultivation using nutrient media. The results of 16S metagenomic analysis showed that Firmicutes and Proteobacteria were predominant bacterial taxons at the phylum level in the intestinal microbiome in both groups of animals, with their numbers being roughly the same. At the bacterial familylevel, the number of Clostridiaceae was a little higher in Aberdeen Angus cows (19.7%) than in the local breed cattle (15.4%). The representatives of the families Bacteroidaceae, Peptococcaceae, Ruminococcaceae and Coriobacteriaceae prevailed in the gut microbial community of local cattle. These microorganisms are involved in the synthesis of vitamins, they stimulate the immune function of the body, normalize digestion, improve nutrient utilization and thus contribute to body weight gain in animals. Small numbers (0.5%) of bacteria of the family Prevotellaceae were detected only in the local breed cows demonstrating high body weight gain. The microbiome of the local cattle was characterized by a considerable diversity at the genus level: the total number of taxons amounted to 65, whereas in Aberdeen Angus cattle it was 40. It was found that the intestinal microbiome of local breed cattle includes less methanogens and more acetogens.